Cartas de amor de Simone de Beauvoir a Nelson Algren : contingência e arrebatamento, necessidade e ruína - Juliana Ferreira da Silva (2024)
This work aims to analyze, in the light of psychoanalysis, the love encounter and its vicissitudes based on the love letters written by Simone de Beauvoir to Nelson Algren and on part of the writer9s autobiographical memories: could her writing have been a possible treatment for a supposed devastation? The coincidence of the terms used in the love pact between Jean-Paul Sartre and Beauvoir – they would be "essential love", while the others would be "contingent loves" –, also used by Lacan to deal with the contingent love encounter that, ineluctably, turns into necessity, thus configuring "the drama of love", will raise other questions, such as: what lies between the ruin of a once brilliant encounter and the rapture of a new encounter? Are contingent loves fundamental to the maintenance of necessary loves? These themes and questions will lead to an intertwining of concepts that include jouissance (female and male one; not-all phallic and phallic one) and absence of the sexual relationship. To deal with love, the theoretical path will begin with Freud and catastrophe, moving on to Lacan and devastation and contemporary commentators on these themes, namely Jacques-Alain Miller (2015a, 2015b), Pierre Naveau (2017) and Marie-Hélène Brousse (2004). There will be, occasionally, moments when a comparison – and contrast – will be made between the love letters sent by the empowered woman of the past (Beauvoir) and the love "letters" (via internet messages) sent by empowered women of today. Keywords: love; letters; contingency; necessity; devastation; rapture; ruin.